DISASTER RISK MANAGEMENT STRATEGY OF THE IMOGIRI ROYAL CEMETERY SITE - Nurul Fadilla Budiana (Kalyanamitra: Journal of Archaeological Resource Management, 2025)
The Imogiri Royal Cemetery Site is a cultural heritage site designated as a provincial-level heritage site by the Governor of the Special Region of Yogyakarta. Managed by the Ngayogyakarta Hadiningrat Sultanate and Kasunanan Surakarta. Beyond its significance ro the Mataram Islamic royal family, the site holds deep cultural identity value for people of Yogyakarta, particulary those in Imogiri. It servesas a destination for religious tourism, historical exploration, and family recreation due to its scenic beauty and cultural importance. However, its preservation is threatened by various natural disasters, such as earthquakes, landslides, and forest fires. It raising the key research question: What disaster risk management strategies can be applied to the Imogiri Royal Cemetery Site? Data was collected through site observations, interview with stakeholders, and literature studies, which were analyzed to identify potential threats. The findings form the basis for a Disaster Risk Management (DRM) strategy tailored to the site, aiming to mitigate both material and non-material losses and ensure its long-term preservation.